2009
DOI: 10.2465/jmps.090622e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insoluble particles on grain growth in polycrystalline ice: Implications for rheology of ice shells of icy satellites

Abstract: Effects of small volume fractions of insoluble particles on grain growth rates of polycrystalline ice were exam ined at 270 K. The presence of approximately 1 vol% of insoluble particles significantly inhibits the grain growth, and this inhibition effect strongly depends on the particle size. The observed grain growth behavior of ice can be reasonably interpreted on the basis of the Zener pinning effect. Our preliminary results suggest that low viscosities due to small grain sizes required for convective insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Theoretically, ductile subsurface flow and convection of warmer ice within large satellites should evolve to a grain size between 30 and 80 mm [ Barr and McKinnon , 2007], which is considerably larger than the grain sizes tested in this and other previous studies [ Schulson and Duval , 2009]. However, contamination of the ice by dust or solutes could reduce the expected size of ice grains by one or two orders of magnitude [ Barr and McKinnon , 2007; Kubo et al , 2009]. In the case of Titan, ice bedrock could form as the result of denudation and exposure of such interior ice by erosion or impact.…”
Section: Discussionmentioning
confidence: 94%
“…Theoretically, ductile subsurface flow and convection of warmer ice within large satellites should evolve to a grain size between 30 and 80 mm [ Barr and McKinnon , 2007], which is considerably larger than the grain sizes tested in this and other previous studies [ Schulson and Duval , 2009]. However, contamination of the ice by dust or solutes could reduce the expected size of ice grains by one or two orders of magnitude [ Barr and McKinnon , 2007; Kubo et al , 2009]. In the case of Titan, ice bedrock could form as the result of denudation and exposure of such interior ice by erosion or impact.…”
Section: Discussionmentioning
confidence: 94%
“…Detailed analysis of ice-age ice has revealed high concentrations of dissolved impurities and large amounts of microparticles compared with Holocene ice (e.g., Paterson, 1991). Impurities in polycrystalline ice restrict grain growth drastically via drag at the grain boundaries (GBs) (Alley and Woods, 1996) and pinning (Kubo and others, 2009), which is known as the Zener pinning effect. Focusing on the remarkable microstructures of the cloudy bands, Miyamoto and others (1999) used samples of the Greenland Ice Core Project deep ice core to investigate ice-flow behavior via laboratory-based uniaxial compression tests.…”
Section: Introductionmentioning
confidence: 99%
“…The grain sizes of the ice used in the deformation experiments by Song and others (2005, 2008) and Hooke and others (1972) were too large for identification of the contribution of GBs. As for the sizes of microparticles, Kubo and others (2009) revealed that the Zener pinning effect and grain growth restriction become more prominent as the particle size becomes smaller. Actually, substantial numbers of submicron-sized particles are present in the Greenland ice cores (e.g., Steffensen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In our standard models, we set the reference viscosity of icy bodies as η ref = 10 14 Pa s. This value is widely used in studies of differentiated icy bodies, including of the thermal evolution of Pluto (e.g., Kamata et al 2019), the orbital evolution of Pluto-Charon (e.g., Renaud et al 2021), and the tidal heating of Europa and Titan (e.g., Tobie et al 2005). However, we note that the reference viscosity of icy bodies strongly depends on the grain size of ice crystals (e.g., Goldsby & Kohlstedt 2001;Kubo et al 2006), and η ref for ice mixed with a small volume fraction of dust grains may be orders of magnitude lower than the canonical value for differentiated ice bodies (e.g., Kubo et al 2009). When the ice viscosity is controlled by diffusion creep, the reference viscosity, η ref , at the reference temperature, T ref = 273 K, is given by (Kalousová et al 2016)…”
Section: Undifferentiated Bodies Made Of Soft Icementioning
confidence: 70%